Comparison of Early T-Cell Precursor and Non-ETP Subtypes Among 122 Chinese Adults With Acute Lymphoblastic Leukemia - Yi Zhang; Yi Zhang; Yi Zhang; Jie-Jing Qian; Jie-Jing Qian; Jie-Jing Qian; Yi-Le Zhou; Yi-Le Zhou; Yi-Le Zhou; Xin Huang; Xin Huang; Xin Huang; et al. (Frontiers in Oncology, 2020)
Background: Adult T-cell acute lymphoblastic leukemia (T-ALL) is a rare hematological malignancy and significantly linked to poor outcomes. Early T-cell precursor (ETP) leukemia is a unique subtype of T-ALL. The aim of this study is to compare the differences between ETP and non-ETP ALLs in China.Methods: We retrospectively analyzed the records of 122 adult T-ALL patients diagnosed and treated at our center between January 2014 and June 2019. All the patients enrolled were categorized into ETP and non-ETP ALL by immunophenotype, and further statistical analyses about clinical data and prognostic factors were performed.Results: Among the 122 cases, the male-to-female ratio was 2.8:1, and the median age is 29 (range, 16–82) years. Except for 10 patients with insufficient immunophenotyping results, 47.3% (53/112) are ETP and 52.7% (59/112) are non-ETP. Compared with non-ETP patients, ETP-ALL patients had lower white blood cell counts and lactate dehydrogenase levels, while they were older and had higher platelet counts and fibrinogen levels (all p < 0.05). Complete remission (CR) was achieved in 68.0% (83/122) of patients, 64.2 and 76.3% in ETP and non-ETP, respectively (p = 0.160). In total, 44.6% (37/83) of patients relapsed. Allogeneic stem cell transplantation (allo-SCT) was successfully performed in 36.1% (44/122) of patients, of which 79.5% (35/44) were in CR1. With a median follow-up of 9.1 (range, 0.5–70.3) months, the estimated 2-year overall survival (OS) and relapse-free survival (RFS) rates for the cohort were 38.0 ± 5.1 and 39.1 ± 6.3%, respectively. In the ETP group, the 2-year OS rate was 40.7 ± 8.2% and the RFS rate was 47.2 ± 10.7%, while in the non-ETP group, the 2-year OS rate was 37.9 ± 7.0% and the RFS rate was 39.2 ± 8.3% (both p > 0.05). In the landmark analysis of CR1 patients who had a survival of more than 6 months, the allo-SCT group had significantly better survival outcomes than the chemotherapy group, and the 2-year OS rates and RFS rates were 80.1 ± 7.3 vs. 28.4 ± 8.4% and 68.9 ± 8.8 vs. 12.8 ± 7.2%, respectively (both p < 0.0001). A multivariate analysis suggests that allo-SCT acts as an independent prognostic factor for both OS and RFS.Conclusions: Our results revealed that ETP accounted for a high proportion of T-ALL in Chinese. There are no CR rates and prognosis differences between ETP and non-ETP. Allo-SCT in CR1 can significantly improve patients' survival.